Playing Victim Dalam Perspektif Hadis Dan Kontekstual Dalam Kehidupan Sosial - Farindra Eka Putra; Sholahuddin Al-Ayubi (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
In modern times, new terms such as "playing the victim" have emerged. This study aims to discuss sacrificial play from the perspective of hadith. This research method uses the qualitative thematic method. Material objects play the victim. A formal course of morals and ethics in social life. The results of the research are summarized in the form of a hadith on victimhood. The discussion of this study explains that victimhood is independent of Islamic values ​​related to morals and ethics in social life, such as honesty, responsibility, etc., which protect the honor of one's fellowmen. The conclusion of this study on victimhood is that victimization is behavior that produces negative effects, is contrary to moral ethics in social life, and does not conform to the second guideline of Islam, the Hadith. be. Because we know that today's social life lacks morals and ethics, but as a social being who cannot live alone and needs other people, it is necessary to behave appropriately. Because there is.